Exploring the relationship between drought-flood abrupt alternation and soil erosion over Guangdong, China through a convection-permitting model - Xuerou Weng; Jinxin Zhu; Dagang Wang; Huijiao Chen; Shuo Wang; Yamin Qing (Geomatics, Natural Hazards & Risk)
Climate change has caused a more heterogeneous distribution of extreme precipitation, leading to the deterioration of drought-flood abrupt alternation (DFAA) events and soil erosion. The security and sustainable utilization of water and soil resources are severely threatened. Previous studies have focused separately on these two aspects, failing to comprehensively consider their interrelationship. Furthermore, these studies often rely on climate models with convection parameterization, resulting in substantial uncertainties. We use a 4 km convective permitting model (CPM) to generate reliable outputs for extreme precipitation. By incorporating the long-cycle drought-flood abrupt transition index and the Revised Universal Soil Loss Equation model, we analyze the changes in DFAA events and soil erosion, as well as their interconnectedness. The results show that the CPM outperforms coarse-resolution climate models in reproducing erosive rainfall and simulating the heterogeneous distribution of rainfall by capturing convection processes effectively. Projections indicate an escalation in the occurrence of DFAA events and soil erosion due to the more uneven distribution of precipitation. Specifically, the frequency of flood-to-drought (FTD) events within DFAA is projected to rise from 3.8 to 4.7 per decade. Soil loss is projected to increase 61 t·hm−2·a−1, with 73% of the area experiencing more severe soil erosion intensity. A positive correlation between FTD events and soil erosion is found throughout most of Guangdong. This correlation will be further amplified with an increase in the frequency of FTD events. Consequently, existing soil conservation measures are rendered inadequate, presenting substantial challenges for climate change adaptation and ecological protection in the region.